Hàm sản xuất một mức với nhịp độ tăng năng suất tới hạn phụ thuộc mọi nhân tố sản xuất - Tú, Tô Cẩm (Journal of Computer Science and Cybernetics, 2016)
By using of rates of limit productivity’s growth dij in this work, the following fundamental theorems for one-level production functions with constant elasticity of substitution are proved. With these sentences the building of all such function is possible. However, for the construction of almost all such functions we have a simple theorem. The smooth function of one –level production function with constant elasticity of substitution is the function with the same constant of elasticity of substitution.